2021
DOI: 10.2147/clep.s304939
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-Reported Diagnosis of Osteoporosis in Japan Nurses’ Health Study

Abstract: Purpose: Although the validity of self-reported osteoporosis is often questioned, validation studies are lacking. This study was performed to investigate how well self-reported diagnoses of osteoporosis agreed with validated clinical information in young and middle-aged women in the Japan Nurses' Health Study (JNHS), a nationwide prospective cohort study of nursing professionals. Patients and Methods: Data were reviewed for 15,717 subjects from the combined cohorts of the JNHS and a preceding pilot study (Gunm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The difference may be that they used fracture incidence, whereas we used fracture prevalence. The reliability of self-reported information may be a problem because errors can be introduced [27], but also national fracture registries have flaws. Optimally, self-reported fractures should be checked against fracture registries, but it was not possible at the time.…”
Section: Discussionmentioning
confidence: 99%
“…The difference may be that they used fracture incidence, whereas we used fracture prevalence. The reliability of self-reported information may be a problem because errors can be introduced [27], but also national fracture registries have flaws. Optimally, self-reported fractures should be checked against fracture registries, but it was not possible at the time.…”
Section: Discussionmentioning
confidence: 99%
“…First, because information regarding the diagnosis of osteoporosis and the incidence of fracture was based on participants’ self-reporting, there might be recall bias. The validity of self-reported versus objectively diagnosed osteoporosis has been considered a problem, and several studies have investigated this issue 28,29 . While one study showed relatively high consistency between self-reporting and objectively diagnosed osteoporosis in the incidence of osteoporosis in Japanese nurses, 28 poor agreement was reported in another study 29 …”
Section: Discussionmentioning
confidence: 99%
“…The validity of self-reported versus LIFESTYLE FACTORS, OSTEOPOROSIS, AND FRACTURE objectively diagnosed osteoporosis has been considered a problem, and several studies have investigated this issue. 28,29 While one study showed relatively high consistency between self-reporting and objectively diagnosed osteoporosis in the incidence of osteoporosis in Japanese nurses, 28 poor agreement was reported in another study. 29 Second, the lack of information regarding when osteoporosis and fracture were detected, as well as the cause of fracture, makes it difficult to interpret the results, especially in Group 4, in which both osteoporosis and fracture occurred during the follow-up period.…”
Section: Limitationsmentioning
confidence: 98%
“…Nevertheless, a recent systematic review, as well as a recent social media survey of PLO, investigated only vertebral fractures [ 14 , 15 ]. In Japan, a few epidemiological studies of osteoporosis in young women have recently been published [ 13 , 16 ], but it is difficult to identify the occurrence of fragility fractures without major trauma in large populations with high anonymity. Toba et al [ 13 ] investigated the epidemiology of PLO using the Japanese Diagnostic Procedure Combination (DPC) database covering about half of all inpatients in Japan, but single fragility fractures are often treated without hospitalization.…”
Section: Introductionmentioning
confidence: 99%